2017
DOI: 10.3899/jrheum.160559
|View full text |Cite
|
Sign up to set email alerts
|

Invalidation in Patients with Rheumatic Diseases: Clinical and Psychological Framework

Abstract: Invalidation occurs in all rheumatic diseases and patients with FM experience the most invalidation. Psychological factors (happiness, agreeableness, and conscientiousness), loneliness, and pain intensity are associated with invalidation, irrespective of the rheumatic disease and may deserve dedicated interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
3
26
3
1
Order By: Relevance
“…Santiago et al found that invalidation occurred in all rheumatic diseases with psychological factors, loneliness and pain intensity associated with invalidation and deserving of dedicated intervention. 16 Our initial research is in agreement with previous research that the reliance amongst many HCPs on often inconclusive test results rather than considering subjective symptoms can leave many patients feeling disbelieved and dismissed. 17,18,19 Price and Walker found that for some the SLE diagnostic journey often has no satisfying conclusion and can be an iatrogenic experience with the journey to diagnosis mirroring the disease in terms of ambiguity and chaos.…”
supporting
confidence: 90%
“…Santiago et al found that invalidation occurred in all rheumatic diseases with psychological factors, loneliness and pain intensity associated with invalidation and deserving of dedicated intervention. 16 Our initial research is in agreement with previous research that the reliance amongst many HCPs on often inconclusive test results rather than considering subjective symptoms can leave many patients feeling disbelieved and dismissed. 17,18,19 Price and Walker found that for some the SLE diagnostic journey often has no satisfying conclusion and can be an iatrogenic experience with the journey to diagnosis mirroring the disease in terms of ambiguity and chaos.…”
supporting
confidence: 90%
“…32,35,66 In line with recent conceptualizations, (mis)attribution of pain as psychological in nature could be considered a form of discounting. 39 Defined by Kool and colleagues 39 as a type of invalidation, discounting responses to pain have been shown to negatively impact the physical and emotional health of individuals with pain conditions, particularly fibromyalgia 25,65 which is known to be more prevalent in women. 80 Our findings, despite their relatively smaller effect sizes, align with those from non-pain studies in which women are more likely to have their physical symptoms dismissed as psychological reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The term “invalidation” is used to describe the patients' perception that their illness and symptoms is not recognized by their social environment [ 24 ]. Although invalidation is not exclusive to FM patients and also affects other rheumatic diseases, it most often perceived and expressed by FM patients [ 25 26 ]. Practicing clinicians are often confronted with a high prevalence of invalidation in FM patients.…”
Section: Main Bodymentioning
confidence: 99%